A Study to Assess Awareness Levels and Status of Lipid Parameters in the Subjects with Coronary Artery Disease in Tertiary Care Setup in a Rural Area - DVSS Ramavataram; Prasad Snehita; Tejas Shah; Sheetal Chhaya; Mishra Mritunjay (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background:-. Among the various cardiovascular diseases, Coronary artery disease is one of the majoretiology of mortality and morbidity in the world wide population. It is a prevalence in mainly older adultsand exists in the entire health context. The CAD prevalence was strongly associated with various lipidparameters such as cholesterol and different lipoprotein fraction, which contributed as a major factor for theprogression of CAD. In spite of various therapeutic advances, so for safe and effective management of CAD,there are requirements for consideration of risk/benefits and goals of care.Objective: To determine the current level of knowledge of the symptoms and duration of diseases and alsocomparison of lipid parameters in cases and control.Material and Methods:-The study was a case control observational study conducted in the department ofbiochemistry, SBKSMI& RC. A total of 200 subjects of 100 Coronary artery disease (CAD) and 100 healthycontrol were enrolled to assess lipid parameter and duration of diseases.Result: - There were 82% male and 18% female in case group and CAD caused majorly by the anginawhich was 65% and in the symptom of duration, majority of people aware with their symptoms in less than1 months. In the measurement of dyslipidemia there was significantly higher in atherogenic component i.e.LDL-C and anti atherogenic component i.e. HDL-C was also higher and found significant.Conclusion: - The majority of subjects who were suffering from CAD were males compared to females.Most of the patients from a rural areas so they had a chest pain comparison to heart attack and found highlysignificant with lipid parameters.